Peer-to-peer electricity trading in China and the EU: A comparative evaluation of key policy documents - Helena Uhde (Research in Globalization, 2022)
Peer-to-peer electricity trading is the exchange of electricity between interconnected participants, such as distributed energy generators, consumers and prosumers. While the term 'peer-to-peer electricity trading' is common in scientific discussions, the term is rarely used in policy language. However, with an increase of distributed energy resources and the need for effective management mechanisms, policy documents of the EU and China in recent years have supported the concept without explicitly using the term. This paper uses qualitative content analysis and examines six relevant policy documents of the EU and China that were issued between 2016 and 2019 to determine to what extent they reflect the concept of the 'peer-to-peer electricity trading' in language and content. Key terms, similarities, and differences in the conceptualisation of peer-to-peer electricity trading in the EU and China are identified. The results show that while the conditions and focus of the documents are different in the EU and China, the concept of peer-to-peer trading is a running theme in both regions.
Keywords: 330; P2P electricity trading; Distributed electricity; Qualitative content analysis; Prosumer